Stem Cell Therapy for Treatment of Stress Urinary Incontinence: The Current Status and Challenges - Shukui Zhou; Kaile Zhang; Anthony Atala; Oula Khoury; Sean V. Murphy; Weixin Zhao; Qiang Fu (Stem Cells International)
Stress urinary incontinence (SUI) is a common urinary system disease that mostly affects women. Current treatments still do not solve the critical problem of urethral sphincter dysfunction. In recent years, there have been major developments in techniques to obtain, culture, and characterize autologous stem cells as well as many studies describing their applications for the treatment of SUI. In this paper, we review recent publications and clinical trials investigating the applications of several stem cell types as potential treatments for SUI and the underlying challenges of such therapy.